ANALYSIS OF THE EFFECTIVENESS OF THE DISTRICT SAVINGS AND LOANS ECONOMIC ENTERPRISES PROGRAM IN IMPROVING COMMUNITY WELFARE IN BONTO-BONTO DISTRICT, MA'RANG DISTRICT, PANGKEP DISTRICT - Ariyadi; Sukmiah (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal